Determination of Mycotoxins and Veterinary Medicines in Duck Flesh and Viscera and Assessment of Their Exposure - Yi Zheng; Yuxin Wu; Huanxin Zhang; Xiaolan Chen; Zaixiang Lou; Huijuan Jing; Chunpeng (Craig) Wan (Journal of Food Quality)
Mycotoxins can accumulate in various feeds and thus may get in duck meat, which may have severe food safety and public health implications. This study examined mycotoxins and veterinary medications in duck meat marketed in eight marketplaces around China. For the determination of mycotoxins, including the mycotoxins aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), aflatoxin M1 (AFM1), T-2 toxin, zearalenone (ZEN), and ochratoxin A (OTA), a liquid-chromatography tandem mass spectrometry (LC-MS/MS) method was validated. Overall, 13 out of 48 samples (27%) presented AFB1, and AFB2 was present in 14 out of 48 samples with positive levels ranging from 0.5 μg/kg (gizzard) to 4.1 μg/kg (lung). Eleven samples were contaminated with AFM1. T-2 was also found in three parts of duck samples (duck gizzard, neck, and lung), and the 5th and 48th samples were contaminated with T-2. ZEN was found in 5 of 48 analyzed samples (10%), and OTA was present in 21 out of 48 samples. The maximum kinds of mycotoxins found simultaneously in duck samples were six in duck lungs. High co-occurrence of mycotoxins was verified in several samples. The detection rate of various veterinary drugs was 0–12.5% in duck meat samples, and the over standard rate was 2.1%. Co-occurrence of veterinary drugs was verified in several samples.